Progressive decrease in the potential usefulness of meningococcal serogroup B vaccine (4CMenB, Bexsero®) in Gipuzkoa, Northern Spain. - Emilio Pérez-Trallero; Olatz Esnal; José M Marimón (PLoS ONE, 2014)
The effectiveness of a vaccine is determined not only by the immunogenicity of its components, but especially by how widely it covers the disease-causing strains circulating in a given region. Because vaccine coverage varies over time, this study aimed to detect possible changes that could affect vaccine protection during a specific period in a southern European region. The 4CMenB vaccine is licensed for use in Europe, Canada, and Australia and is mainly directed against Neisseria meningitidis serogroup B. This vaccine contains four main immunogenic components: three recombinant proteins, FHbp, Nhba and NadA, and an outer membrane vesicle [PorA P1.4]. The allelic distribution of FHbp, Nhba, NadA, and PorA antigens in 82 invasive isolates (B and non-B serogroups) isolated from January 2008 to December 2013 were analyzed. 4CMenB was likely protective against 61.8% and 50% of serogroup B and non-B meningococci, respectively, in the entire period, but between 2012 and 2013, the predicted protection fell below 45% (42.1% for serogroup B isolates).The observed decreasing trend in the predicted protection during the 6 years of the study (Χ2 for trend  = 4.68, p = 0.03) coincided with a progressive decrease of several clonal complexes (e.g., cc11, cc32 and cc41/44), which had one or more antigens against which the vaccine would offer protection.